Local tumour control after radiofrequency or microwave ablation for colorectal liver metastases in relation to histopathological growth patterns. Issue 9 (September 2022) - Vles, Mark-Jan D.; Höppener, Diederik J.; Galjart, Boris; Moelker, Adriaan; Vermeulen, Peter B.; Grünhagen, Dirk J.; Verhoef, Cornelis
Abstract: Background: Regrowth after ablation is common, but predictive factors for local control are scarce. This study investigates whether histopathological growth patterns (HGP) can be used as a predictive biomarker for local control after ablation of colorectal liver metastases (CRLM). Methods: Patients who received simultaneous resection and ablation as first treatment for CRLM between 2000 and 2019 were considered eligible. HGPs were determined on resected CRLM according to international guidelines and were classified as desmoplastic or non-desmoplastic. As minimal inter-tumoural heterogeneity has been demonstrated, the HGP of resected and ablated CRLM were presumed to be identical. Local tumour progression (LTP) was assessed on postoperative surveillance imaging. Uni- and multivariable competing risk methods were used to compare LTP. Results: In total 221 patients with 443 ablated tumours were analysed. A desmoplastic HGP was found in 60 (27.1%) patients who had a total of 159 (34.7%) ablated lesions. Five-year LTP [95%CI] was significantly higher for ablated CRLM with a presumed non-desmoplastic HGP (37% [30–43] vs 24% [17–32], Gray's-test p = 0.014). On multivariable analysis, a non-desmoplastic HGP (adjusted HR [95%CI]; 1.55 [1.03–2.35]) was independently associated with higher LTP rates after ablation. Conclusion: HGP is an independent predictor of local tumour progression following ablation of CRLM.